Optimal caliper placement: manual vs automated methods. (22nd December 2013) - Yazdi, B.; Zanker, P.; Wagner, P.; Sonek, J.; Pintoffl, K.; Hoopmann, M.; Kagan, K. O.
ABSTRACT Objective To examine the inter‐ and intraoperator repeatability of manual placement of calipers in the assessment of basic fetal biometric measurements and to compare the results with those of an automated caliper placement system. Methods We used stored ultrasound images of 95 normal fetuses between 19 and 25 weeks' gestation. Five operators (two experts, one resident and two students) were asked to measure the biparietal diameter (BPD), occiptofrontal diameter (OFD), abdominal circumference (AC) and femur length (FL) twice manually and twice automatically. For each operator, the repeatability of manual and automated measurements was assessed using intraoperator SD. For the assessment of interoperator repeatability, the mean of the four manual measurements by the two experts for each fetus was used as the gold standard. The relative bias of the manual measurements of the three non‐expert operators and the operator‐independent automated measurement were compared with the gold standard measurement by mean and 95% CI. Results In 89.5% of the 95 cases, the automated measurement algorithm was able to obtain appropriate measurements of BPD, OFD, AC and FL. Intraoperator SDs for the manual measurements ranged between 0.15 and 1.56, irrespective of the experience of the operator. For the automated biometric measurement system, there was no difference between the measurements of each operator. Regarding interoperator repeatability, the mean difference between the manual measurements of the two students, the resident and the gold standard was between −0.10 and 2.53 mm. The automated measurements tended to be closer to the gold standard, but the difference in bias in automated vs manual measurements did not reach statistical significance. Conclusion In about 90% of cases, it was possible to obtain basic biometric measurements with an automated system. The use of automated measurements resulted in a significant improvement in intraoperator repeatability, but measurements were not significantly closer to the gold standard of expert examiners. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.